A model to integrate urban river thermal cooling in river restoration. (15th March 2020) - Abdi, Reza; Endreny, Theodore; Nowak, David
Abstract: River water quality and habitats are degraded by thermal pollution from urban areas caused by warm surface runoff, lack of riparian forests, and impervious channels that transfer heat and block cool subsurface flows. This study updates the i-Tree Cool River model to simulate restoration of these processes to reverse the urban river syndrome, while using the HEC-RAS model water surface profiles needed for flood hazard analysis in restoration planning. The new model was tested in a mountain river within the New York City drinking water supply area (Sawmill, SM, Creek), and then used for base case and restoration scenarios on the 17.5 km reach of the Los Angeles (LA) River where a multi-million dollar riverine restoration project is planned. The model simulated the LA River average temperature in the base case decreased from 29.5 °C by 0.3 °C when warm surface inflows were converted to cooler groundwater inflows by terrestrial green infrastructure; by 0.7 °C when subsurface hyporheic exchange was increased by removal of armoring and installation of riffle-pool bedforms; by 3.6 °C when riparian forests shaded the river; and by 6.4 °C when floodplain forests were added to riparian forests to cool surface reservoirs and local air temperatures. Applying all four restoration treatments lowered river temperature by 7.2 °C. The simulated decreases in river temperature lead to increased saturated dissolved oxygen levels, reaching 8.7 mg/L, up from the 7.6 mg/L in the base case scenario, providing improved fish habitat and reducing eutrophication and hypoxic zones. This study evaluating the performance of environmental management scenarios could help managers control the thermal pollution in rivers. Highlights: i-Tree Cool River was updated to capture thermal impact of river basin restoration on river flows estimated by the HEC-RAS. The simulated Los Angeles River temperature was lowered by 3% by green infrastructure and riffle-pool bedforms. When riparian shading was added to other two restoration scenarios, the simulated LA River temperature was lowered by 14%. Floodplain forest expansion with other restoration scenarios, lowered the simulated LA River. temperature was by 25%.